Epidemiology and antimicrobial resistance of pathogens in pediatric sinus infections: a retrospective study at a Japanese otolaryngology clinic (2023–2025) - Kitaya, Shiori; Kikuchi, Toshiaki; Nomura, Kazuhiro; Nomura, Yuri; Ikeda, Ryoukichi; Kanamori, Hajime; Katori, Yukio (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionHaemophilus influenzae and Streptococcus pneumoniae are two of the major pathogens responsible for pediatric rhinosinusitis. Rising antimicrobial resistance (AMR) and pneumococcal serotype replacement have complicated treatment decisions. This study aimed to investigate bacterial distribution and AMR patterns in nasal discharge samples from children at a Japanese otolaryngology clinic.MethodsWe conducted a retrospective study at an otolaryngology clinic in Sendai, Japan, from February 2023 to March 2025. A total of 2009 nasal discharge specimens were analyzed. Bacterial identification and antimicrobial susceptibility testing were performed according to Clinical and Laboratory Standards Institute guidelines. H. influenzae and S. pneumoniae were phenotypically classified and stratified by age (0-2, 3-5, and 6-13 years). Age-group comparisons were performed using Fisher’s exact test with Holm correction.ResultsPathogens were detected in 1862 samples (92.7%). The most frequently isolated organisms were Moraxella catarrhalis (30.9%), H. influenzae (23.0%), and S. pneumoniae (20.6%). Among the 697 H. influenzae isolates, 44.8% were ampicillin-resistant, and 31.3% of all isolates were β-lactamase-negative ampicillin-resistant (BLNAR) strains. Some BLNAR strains exhibited reduced susceptibility to amoxicillin–clavulanic acid (MIC90 = 8 μg/mL). Cefotaxime, cefditoren, and levofloxacin remained highly active. Among the 625 S. pneumoniae isolates, 66.6% were penicillin-susceptible, 31.0% were intermediate, and 2.4% were resistant; resistance to clarithromycin was observed in 84.3% of isolates. The prevalence of Staphylococcus aureus increased with age, with 25% of isolates in the 6-13-year group identified as methicillin-resistant.ConclusionH. influenzae and S. pneumoniae remain key pathogens in pediatric rhinosinusitis and exhibit high AMR rates. Age-specific trends, including increased methicillin-resistant S. aureus in older children, should guide empiric therapy. Ongoing AMR surveillance and culture-based management are essential.